Ionized magnetron sputtering of Al₂O₃ - Gonzalez, Patrick F., author; Collins, George, advisor; Lile, Derek, committee member; Edwards, Harry W., committee member; Chen, Tom, committee member (Colorado State University. Libraries, 2000)
This dissertation shows a detailed study of the conditions necessary for sputtering alumina using a novel variant of ionized magnetron sputtering (IMS) first demonstrated by Yamashita et. al. The study presented herein leverages concurrent research at our laboratory on high density plasmas, plasma characterization and charged particle beams research to demonstrate a new source capable of sputtering hydrated alumina films at high rates. High quality ceramics such as Al2O3 find uses in a variety of applications, and in particular, for mass storage applications. Consequently, there exists an ever-growing need to provide and improve the capability of growing thick insulating films. Ideally, the insulating film should be stoichiometric and able to be grown at rates high enough to be easily manufacturable. Alumina is a particularly attractive due to its high density, Na barrier properties, and stability and radiation resistance. However, high quality films are often difficult to achieve with conventional RF plasma due to extremely slow deposition rates and difficulties associated with system cooling. The preferred method is to reactively sputter Al from a solid target in an O2 ambient. Nevertheless, this process is inherently unstable and leads to arcing and uneven target wear when magnetrons are used. In this study, we build the sputtering source, evaluate, and maximize the deposition characteristics of alumina films sputtered from a solid target in an Ar/O2 ambient. Semi-crystalline (κ + θ) alumina has been reported using a similar technique at temperatures as low 370 C. The difference in the system used herein is that RF power is used for both, the inductive and capacitive components. Additionally, we use a solid target made of sintered alumina throughout the experiment. A model is developed using regression analysis and compared to results obtained. Because plasma parameters can interact with each other, we explore ICP/CCP power interactions and gas influence on deposition. The design and analysis is done using RS/1, which is the industry standard for statistical analysis. Results of this study indicate the ability to grow Al2O3 at rates close to 200 A/min. The samples analyzed via ESCA show a perfect match cc the most common hydrated phases of alumina. XRD analysis indicates the films to be amorphous, but that is not unexpected given the low temperature at which the films were grown. Film properties are shown to be a function of the current density flux set up by the ICP source, and the ion energy to the target as determined by the CCP source.
Ionized magnetron sputtering of aluminum2oxygen3
Keywords: materials science; fluid dynamics; gases; plasma physics